(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper deals with the current and future aspect of E-commerce in Indian context and also Here, we will discuss how internet marketing plays a vital role aiming at promoting the ranking of websites in the search engine’s search results page which can make a web site introduce into more web users and website traffic.in this paper we will also emphasis on various techniques of internet marketing eventually we will conclude on pros and cons of the bussiness on internet.